Peranan Prajurit Bintaljarahdam Sebagai Representasi Moderasi Beragama di Wilayah Kodam XIII/Merdeka - Juberth Nixon Purnama; Jeane M. Tulung; Wolter Weol (Peneliti.net, 2022)
This study aims to obtain the results of the analysis and description of (1) Kodam Mental and Historical Development Soldiers in realizing representations of religious moderation in the Kodam XIII / Merdeka area, (2) Obstacles to soldiers mental and historical development of kodam in realizing representation of religious moderation in the Kodam XIII / Merdeka area, and (3) Efforts of soldiers mental development and history of kodam in realizing representation of religious moderation in the area of Kodam XIII / Merdeka. This research approach is qualitative by using data collection techniques: (1) observation, (2) in-depth interviews and (3) documentation, equipped with unstructured interviews, cameras, photos, recording devices and field notes. Data analysis uses steps (1) data reduction, (2) Display Data and (3) checking the validity of data.Based on the results of the analysis, was reached (1) Religious moderation is a way of view or religious attitude and practice that practices the essence of religious teachings that essentially contain human values and spread mutual benefit (avoid radicalism and intolerance). The Army soldiers in it the Kodam Mental and Historical Development unit (Bintaljarahdam) certainly serve as a means of state defense must be able to realize religious moderation in the practice of living every day in the Kodam XIII / Merdeka area. (2). This religious moderation in practice must be carried out holistically in terms of ethics, sociology, anthropology and psychology as well as IPOLEKSOSBUDHANKAM (Asta Gatra), so as to avoid the emergence of negative effects as an obstacle that can affect the lives of especially soldiers in the implementation of basic tasks. . (3) Efforts are urgently needed for the optimal implementation of religious moderation, taking into account principles, conditions, perspectives, attitudes and practices as well as characteristics accompanied by knowledge, attitudes, skills